2022
DOI: 10.1039/d2nj02315f
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the catalytic activity of Nb4C3Tx MXene towards the degradation of nitro compounds and organic dyes by in situ decoration of palladium nanoparticles

Abstract: We report on the catalytic activity of Nb4C3Tx based composites towards the catalytic reduction of nitro compounds and organic dyes for the first time. Nb4C3Tx-PdNPs composite has been synthesized by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…MXene, one of the youngest members in the 2D materials family, possesses unique features such as exceptional electrical conductivity and hydrophilicity, making them extremely promising candidates for a wide range of applications like energy storage, environmental remediation, and diagnostic applications. , It was established that MXene can be used to make the composites with MOF to enhance their electrocatalytic activities toward electrochemical sensing applications. The recently reported literatures show many MOF–MXene composites that have shown excellent conductivity and are explored in various electrochemical applications .…”
Section: Introductionmentioning
confidence: 99%
“…MXene, one of the youngest members in the 2D materials family, possesses unique features such as exceptional electrical conductivity and hydrophilicity, making them extremely promising candidates for a wide range of applications like energy storage, environmental remediation, and diagnostic applications. , It was established that MXene can be used to make the composites with MOF to enhance their electrocatalytic activities toward electrochemical sensing applications. The recently reported literatures show many MOF–MXene composites that have shown excellent conductivity and are explored in various electrochemical applications .…”
Section: Introductionmentioning
confidence: 99%
“…Rasheed et al reported the catalytic activity of Nb 4 C 3 T x @PdNP MXene composites towards the reduction of 4-nitrophenol and organic dyes. 32 About 200 μL of 0.5 mg mL −1 Nb 4 C 3 T x @PdNP catalyst was added to 400 μL of 1 mM 4-NP in the presence of NaBH 4 , which reduced 4-NP within 3 min and the catalyst was reused for up to 5 consecutive cycles without much loss in the catalytic activity. Chen et al prepared CQD@Ag/Ti 3 C 2 MXene composites and used them to catalyse the reduction of 4-NP.…”
Section: Introductionmentioning
confidence: 99%